2013
DOI: 10.1080/02640414.2013.815361
|View full text |Cite
|
Sign up to set email alerts
|

Adolescent pedometer protocols: examining reactivity, tampering and participants’ perceptions

Abstract: The aim of this study was to investigate adolescents' potential reactivity and tampering while wearing pedometers by comparing different monitoring protocols to accelerometer output. The sample included adolescents (N = 123, age range = 14-15 years) from three secondary schools in New South Wales, Australia. Schools were randomised to one of the three pedometer monitoring protocols: (i) daily sealed (DS) pedometer group, (ii) unsealed (US) pedometer group or (iii) weekly sealed (WS) pedometer group. Participan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
31
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(33 citation statements)
references
References 33 publications
2
31
0
Order By: Relevance
“…Previous studies have also found this to be a challenge. As outlined earlier, Scott et al (2014) found low wear-time compliance among youth participants, particularly with waist-worn devices along with evidence of reactivity and device tampering. Another recent study found approximately 31% of boys and girls did not meet wear-time compliance when measuring physical activity using an arm-worn (worn on the upper arm/triceps area) accelerometer (Saint-Maurice, Kim, & Welk, 2017).…”
Section: Limitationssupporting
confidence: 52%
See 2 more Smart Citations
“…Previous studies have also found this to be a challenge. As outlined earlier, Scott et al (2014) found low wear-time compliance among youth participants, particularly with waist-worn devices along with evidence of reactivity and device tampering. Another recent study found approximately 31% of boys and girls did not meet wear-time compliance when measuring physical activity using an arm-worn (worn on the upper arm/triceps area) accelerometer (Saint-Maurice, Kim, & Welk, 2017).…”
Section: Limitationssupporting
confidence: 52%
“…However, sensitivity analyses showed participants wearing the Actigraph accelerometer for 6 hours per day participated in daily MVPA significantly more than those who met the standard 10 hours per day criterion. In general, the objective measurement of MVPA among children and youth is a challenging endeavor, with studies suggesting that reactivity (change in normal behavior) and tampering influence the data (Scott, Morgan, Plotnikoff, Trost, & Lubans, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although these strategies were employed in the ATLAS intervention, only 30% of participants wore their pedometers regularly. In a previous study, Scott and colleagues (45) found that many young people did not enjoy wearing objective monitoring devices such as pedometers and accelerometers and it is possible that participants in the current study were reluctant to wear the devices for self-monitoring purposes. While not feasible in the current study, apps that take advantage of a phone’s inbuilt accelerometer (e.g., “Moves”) may have more utility for promoting self-monitoring in young people.…”
Section: Discussionmentioning
confidence: 83%
“…Our research team has employed a range of strategies to improve compliance with accelerometer protocols, including: (a) providing participants with accelerometer logs and stickers reminding participants to wear their devices; (b) sending automated text messages to participants and their parents (for youth) each morning to remind them to wear their accelerometers; and (c) providing small incentives (e.g., sports socks, water bottles) for those who adhere to the protocols and return their accelerometers undamaged. The measurement of physical activity using pedometers presents additional challenges because unlike accelerometers, pedometers provide feedback to participants, which can result in reactivity (Scott, Plotnikoff, Lubans & Morgan, in press).…”
Section: Approach and Discussionmentioning
confidence: 99%